Efficacy and Safety of Recombinant Human Thrombopoietin on Sepsis Patients With Thrombocytopenia: A Systematic Review and Meta-Analysis - Zhang, Jin; Lu, Zongqing; Xiao, Wenyan; Hua, Tianfeng; Zheng, Yao; Yang, Min (Frontiers in Pharmacology, 2020)
Background The efficacy and safety of the administration of recombinant human thrombopoietin (rhTPO) in sepsis patients with thrombocytopenia were still inconclusive. Objectives To investigate whether rhTPO is a benefit for sepsis patients with thrombocytopenia. Methods PubMed, Cochrane library, Embase, China National Knowledge Infrastructure, and Wanfang Database were electronically searched to the randomized controlled trials (RCTs) from inception to March 4, 2020. The primary outcome was the level of platelet (PLT) on the 7th day of treatment, and secondary outcomes were 28-d mortality, the level of coagulation indicators, hepatic and renal function indicators, blood transfusion, and length of intensive care unit (ICU) stay. Results Ten RCTs involving 681 patients were included. For compared with conventional antibiotic therapy, rhTPO could significantly increase platelet counts (PCs) [standardized mean difference (SMD), 2.61; 95% confidence interval (CI), 1.28–3.94; P < 0.001], decreased 28-d mortality [relative risk (RR), 0.66; 95%CI, 0.46–0.97; P=0.03], transfusion volume of blood products and length of ICU stay. Additionally, for compared with conventional antibiotic therapy combined with intravenous immunoglobulin, the pooled results shown that rhTPO also associated with an improvement of PCs on 7th of treatment (SMD, 0.86; 95%CI, 0.54–1.17; P < 0.001), and a reduced transfusion volume of blood products. However, there were no differences in 28-d mortality and the length of ICU stay. Conclusions Current evidence shown that rhTPO could increase PCs on 7th day of treatment and reduce the transfusion volume of blood products in sepsis-related thrombocytopenia during hospitalization. The conclusions are needed to be verified indeed by more multicenter RCTs due to the limitation of the included studies.